2002
DOI: 10.1039/b205781f
|View full text |Cite
|
Sign up to set email alerts
|

Changeable reactivity of ketyl radicals derived from 2-bromomethyl-2-(3-butenyl)benzocyclic-1-alkanones depending on electron transfer conditions employed

Abstract: Photoinduced electron transfer reaction of 2-bromomethyl-2-(3-butenyl)benzocyclic-1-alkanones with amines afforded 5-exo radical cyclization products while electron transfer reaction with samarium diiodide produced cyclopropanols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Either external or internal bond cleavage of 8 generates the respective primary alkyl radical 9 or tertiary alkyl radical 10 . An equilibrium interconverting 9 and 10 through 8 [2230] might occur (see below). A mechanism on the fragmentation of initially formed metal–organic complexes, giving β-ketoalkyl radicals [40], cyclopropoxy radicals [25,28,4850], or β-metalated carbonyls [39], is still controversial [3547].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Either external or internal bond cleavage of 8 generates the respective primary alkyl radical 9 or tertiary alkyl radical 10 . An equilibrium interconverting 9 and 10 through 8 [2230] might occur (see below). A mechanism on the fragmentation of initially formed metal–organic complexes, giving β-ketoalkyl radicals [40], cyclopropoxy radicals [25,28,4850], or β-metalated carbonyls [39], is still controversial [3547].…”
Section: Resultsmentioning
confidence: 99%
“…1) that act as radical ion probes [20] and found that radical intermediates in their reaction pathways undergo efficient 5- exo hexenyl radical cyclization reactions [21], (Fig. 1) [2230]. For example, PET reactions of probe I with amines were observed to produce a spirocyclic ketone product while its reduction reaction induced by samarium diiodide (SmI 2 ) gives rise to a cyclopropanol (left in Scheme 3) [22,24,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary observation that the irradiation of 1a with DMPBI predominantly produced 2a in aqueous MeCN was reported 4c…”
Section: Referencesmentioning
confidence: 99%
“…Photoinduced electron transfer (PET) reactions that generate radical intermediates represent attractive alternative approaches for promoting Beckwith–Dowd ring expansion processes under mild and eco-friendly conditions. Although methods involving PET-promoted Beckwith–Dowd ring expansion reactions of halomethyl substituted benzocyclic ketones with amines and of α-bromomethyl β-keto esters by using a B 12 –TiO 2 hybrid catalyst have been described, both approaches require the use of haloketones as reactants and generate environmentally unfriendly hydrogen halides.…”
mentioning
confidence: 99%